(untitled) (Forum Theologicum Sardicense, 2025)
The aim of this article is to raise the issue of the spelling of the phrases “Holy Scripture,” “Old Testament,” and “New Testament” within the scien-tific community. The problem is both linguistic and theological in nature, as it concerns concepts fundamental to theological knowledge. However, discrepancies in the spelling of these terms in textbooks across different subjects hinder the work of both students and teachers, leading to a lack of consistent pedagogical influence.